Role of complement activation in anti-neutrophil cytoplasmic antibody-associated glomerulonephritis - Kojima, Tadasu; Oda, Takashi (Frontiers in Medicine, 2022)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (AAGN) is a critical kidney disease clinically characterized by rapidly progressive glomerulonephritis (RPGN). The primary histological features in the kidneys of AAGN patients are classified as pauci-immune necrotizing crescentic glomerulonephritis, which refers to little or no deposition of immunoglobulins or complement components; hence, the role of complements in AAGN has been overlooked for a long time. However, substantial evidence, both in mice and humans, has recently demonstrated the crucial role of complement activation in the pathogenesis of AAGN. Previous studies have suggested that the complement system, especially activation of the alternative pathway (AP), plays an important role in the development of AAGN. Circulating and urinary detection of various complement components associated with AP activation, which have been broadly correlated with the clinical activity of AAGN, have been reported and may be useful for predicting renal outcome at diagnosis and setting up personalized treatments. Moreover, recent investigations have suggested the possible contribution of complement classical or lectin pathway activation in the development of AAGN. Thus, the primary complement pathway involved in AAGN remains to be elucidated. 　As therapeutic options targeting complement components are making rapid strides, elucidating the precise complement activation pathway in AAGN disease progression would directly impact the development of novel therapeutic strategies with high specificity and reduced side effects. This review summarizes and discusses the most recent evidence on the roles of complement activation in the pathogenesis of AAGN and possible therapeutic strategies that target complement components for disease management.